A Rare Encounter: Gastric Ulcer Penetration into the Splenic Hilum Presenting with Upper Gastrointestinal Bleeding and a Massive Splenic Haematoma—Case Report and Literature Review - Ioana-Irina Rezuș; Vasile-Claudiu Mihai; Diana Elena Floria; Andrei Olteanu; Vlad Ionut Vlasceanu; Radu Petru Soroceanu; Alin Constantin Pinzariu; Brigitta Teutsch; Sergiu Tudose-Timofeiov (Diagnostics)
Background: Despite advancements in prevention and treatment, peptic ulcer disease (PUD) remains a public health burden, with potentially high mortality rates when not managed properly. Recent studies indicate bleeding as the most prevalent complication, followed by perforation or penetration into adjacent organs and pyloric obstruction. In rare cases, posterior wall or greater curvature ulcers of the stomach can penetrate, leading to splenic artery pseudoaneurysms. With nonspecific symptoms and low incidence, it is highly important that these entities are not overlooked in the diagnosis of patients with upper gastrointestinal bleeding. Case Report: We present the case of a 44-year-old patient presenting for upper abdominal pain and haematemesis while being haemodynamically stable. Emergency ultrasound described a dysmorphic spleen, with a transonic image with a Doppler signal in the splenic hilum. Upper gastrointestinal tract endoscopy detected a blood-filled stomach, without the possibility of identifying the bleeding source. The CT scan revealed active bleeding with peri splenic haematoma. Intraoperatively, a posterior gastric wall penetration into the spleen was identified, and an atypical gastric resection and caudal splenopancreatectomy were performed. The postoperative course was marked by the identification of a staple line leak in the upper pole of the stomach, which was treated conservatively, with a favourable outcome, and the patient was discharged after two weeks. Conclusions: Upper gastrointestinal tract haemorrhage needs fast intervention and suitable management. The multidisciplinary team plays a key role in identifying and treating rare causes such as penetration into the splenic hilum.